ANALISA SISTEM PENGENDALIAN INTERN PENGGAJIAN PADA BADAN NASIONALPENGELOLA PERBATASAN REPUBLIK INDONESIA JAKARTA - Hartoko, Muhammad Setiadi (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2014)
Role of the newly formed state is very strategic. Analysis is done to manage the assignment of functional personnel and employee payroll and perform pattern in accordance with existing procedures. National Agency for Border Management is in the auspices of the Departmentof the Interior as the agency that handles strategic territorial borders of the Republic of Indonesia. Analysis of internal controls related to the payroll system supporting staff(other than civil servants, recruited from the general public) to manage general administration in accordance with applicable regulations where the process of collecting data through interviews, observations and literature. Results achieved BNPP RI is sufficient and successfully implement functional process payroll with good internal control. Grooves and patterns are part of the groove payroll administration managed to smooth operation of supporting staff. Keywords: Internal Control, SupportingStaff, BNPPRI, personnel.